Pengembangan Sistem Monitoring Kanal Air sebagai Sarana Penanggulangan Banjir - Othman Mirizi Batubara; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Floods is one of the most common natural disasters in the Asian region. Based on statistical data of the National Disaster Management Agency (BNPB) on 2009-2018, it was noted that the number of dead and missing victims over 11 thousand people. A monitoring system is needed that can quickly and accurately provide information and warnings to the public. Therefore, the researchers conducted a study entitled the development of a water canal monitoring system as a flood mitigation. To realize a monitoring system, a protocol for network communication is required. Hypertext Transfer Protocol (HTTP) is a protocol that allows communication between the ESP8266 which uses a client and server architecture with centralized control. HTTP POST request-response method can be used for the communication method between WiFi client nodes and WiFi server nodes. The system stores sensor data in a Firebase database connected to the android application. The android application can provide notification alerts to the user if the system detects a danger. Based on the test results, it was concluded that NodeMCU ESP8266 can communicate with each other using the HTTP POST method. From the sensor test, the average error result is 17.86%. In testing the delay of sending data between nodes at a distance of 5m, 30m, 50m, 80m and 100m, it has an average delay of 242.17ms, 964.4ms, 979.3ms, 988.9ms and 997.0ms. In testing the android application the system can display the results of system monitoring and the user gets a warning notification when the system detects a potential hazard.